Child stunting concurrent with wasting or being overweight: - Iversen, O. Per; Ngari, Moses; Westerberg, C. Ane; Muhoozi, Grace; Atukunda, Prudence (Elsevier Inc., 2021)
Objectives: There is paucity of longitudinal data on combined anthropometric deficiencies in children. Herein, we present data on child stunting concurrent with wasting or being overweight among children in a 6-y follow-up study of a maternal education trial in rural Uganda. Methods: We previously performed a randomized controlled trial where half of 511 mothers of 6- to 8-mo children were given a 6-mo education concerning nutrition, hygiene, and child stimulation. Anthropometry and prevalence of stunting with wasting or being overweight were determined. We applied multilevel mixed-effect logistic regression models and x2 statistic to assess the effects of the intervention and trend in prevalence over time, respectively. Results: Complete data sets were obtained from 307 of 511 children (60%). The prevalence of stunting and wasting or being overweight was <7% both, and did not change significantly over time. Notably, the prevalence of concurrent stunting and being overweight was significantly reduced in the intervention group compared with the controls among children age 36 mo and 60 to 72 mo, with corresponding odds ratios at 0.24 (95% confidence interval, 0.060.90) and 0.10 (95% confidence interval, 0.010.82), respectively. Conclusions: The prevalence of stunting concurrent with wasting or being overweight remained low during the observation period. The intervention may have reduced concurrent stunting and being overweight over time. Keywords: Anthropometry, Children, Maternal education, Overweight, Randomized trial, Stunting, Uganda, Wasting
A 6-y follow up of a randomized maternal education trial in Uganda
Article